Perlindungan Hukum atas Kesehatan Mental Pengemudi Transportasi Online dalam Konteks Regulasi Kemitraan Digital - Naila Shafa (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
Abstract This study analyzes the legal construction of partnerships in Permenhub Number 12 of 2019 regarding the protection of the normative rights of online transportation drivers amid regulatory uncertainty. Using a normative doctrinal method with a legislative and literature approach, the results show that the concept of partnership in Permenhub is not in line with the reality of algorithm-based digital work. The power imbalance between platforms and drivers causes psychosocial pressure and economic uncertainty. Therefore, adaptive legal reform is needed to recognize the status of platform workers and ensure sustainable normative protection through stronger algorithmic oversight.